Perinatal and Neonatal Outcomes of Grand Multiparous Refugee Women Under the Age of Thirty-Five: A Comparative Study - Hakan Kizilet; Sonay Oztas; Ercan Comert; Mehmet Murat Isikalan; Talip Karacor (Gynecology Obstetrics & Reproductive Medicine, 2026)
OBJECTIVES: To compare maternal and neonatal outcomes between grand multiparous Syrian refugee women younger than 35 years and Türkiye citizens. STUDY DESIGN: In this retrospective cohort study we screened electronic birth records according to predefined eligibility criteria. Of 313 potentially eligible women, 16 were excluded because their patient files could not be accessed, leaving 297 grand multiparous women aged 18–34 years (150 Türkiye citizens and 147 Syrian refugees) who delivered at Adiyaman University Faculty of Medicine Education and Research Hospital. Women aged